Perang Uhud (Suatu Analisis Historis Sebab-Sebab Kekalahan Umat Islam) - Iqbal Iqbal (Universitas Islam Negeri Alauddin Makassar, 2014)
This paper explain about Uhud War, an accident was happening on Syawwal 07th, 03 H./625 M. On the war, two groups were fighting each other, Moslems and Quraisy Clan. This paper explain on the history side and doing on qualitative research type by library research. Uhud War is the second war after Badar War. On this war, Moslem was losing. This drubbing was happening cause some Moslems wasn’t loyal to prophet’s command. This accident made Hamzah died and prophet Muhammad saw. was hurt by Quraisy Clan. So, Uhud War is the war had been a training for Moslems, including some Moslems supporter had gotten out from Moslem’s line. This group was commanded by Abdullah Bin Ubay. They were going back to Madinah before the war happened. This accident absolutely made account of Moslems had decreased. At the beginning of war, prophet Muhammad had thousand warriors, but after this accident, prophet Muhammad had seven hundred warriors. This accident absolutely had decreased to the power of warriors.